Importance of the formation of value added sequence as part of the industrial and innovative development (Journal of Economic Research & Business Administration, 2016)
The relevance of manufacture of products with high added value arisesfrom the conditions and requirements of the scientifically and economicallyimportant market economy. The amount of added value, as an economiccategory, is used to determine the efficiency of manufacture. Addedvalue is a difference between the cost of products sold by a company, andthe cost of materials purchased by a company to manufacture products.In other words, added value is an extra added value in the processing ofgoods in promoting them to the market. Added value is a product derivedas a result of social, personal labor or a result of activity of many manufacturers.Since added value is calculated as the difference between thegoods sales’ proceeds and the cost of raw materials and services, used inthe manufacture of goods, if we reduce the cost of current raw materials,energy and other material and technical resources, this will increase theamount of total added value, and will respectively improve the resultingeffect of an industrial complex.
Keywords: value chain; technology; innovation; infrastructure; investment.